Meningkatkan Minat Belajar Siswa Kelas VIII SMPN 2 Pematang Karau pada Pembelajaran IPA Materi Gerak Tumbuhan Menggunakan Media Foto Handphone - Amir Amir (Program of Biology Education, Universitas Lambung Mangkurat, 2019)
In science learning, the material is not contextual, most teachers still carry out traditional learning, teacher centered learning, and explains the photos in the book without giving a real picture in the environment. The situation has the potential to cause boredom, reduce interest, motivation, and deep meaning of what students are learning. The purpose of this study was to describe the increase in learning interest of eighth grade students of SMPN 2 Pematang Karau on plant movement material using mobile photo media. The research method uses action research which consists of 2 cycles. The results showed that learning on plant movement material with mobile photo media became more optimal and the learning outcomes of students increased in interest in learning, cognitive aspects, cheerfulness, enthusiasm, attention, and activities.